In vitro and in vivo anti-inflammatory effects of different extracts from Epigynum auritum through down-regulation of NF-κB and MAPK signaling pathways. (28th October 2020) - Yang, Meilian; Wang, Yudan; Patel, Gopal; Xue, Qingwang; Singor Njateng, Guy Sedar; Cai, Shengbao; Cheng, Guiguang; Kai, Guoyin
Abstract: Ethnopharmacological relevance: Epigynum auritum has been historically used as a "dai" or traditional medicine for the treatment of inflammation, swelling and severe pain during injury; these may reduce risk of disease and lead to healthier aging. Apart from this, Epigynum auritum extract was also used in arhritis treatment which is also a type of inflammation. Previous phytochemical studies of E. auritum revealed that steroids are main characteristic components with a number of biological activities (especially immunosuppressive and anti-inflammatory activity) Nevertheless, the underlying mechanism of the E. auritum on inflammatory diseases is still unresolved. Aim of the study: This study aimed to comparatively investigate the anti-inflammatory potential of different fractions from the extract of E. auritum (EAE), with their possible active ingredients to reveal the underlying mechanism. Materials and methods: The EAE was fractionated by column chromatography with macroporous resin D101 which yielded six fractions. The potential anti-inflammatory properties of different fractions of EAE were evaluated in in vitro and in vivo model. The lipopolysaccharide (LPS)-induced RAW264.7 macrophages cells were used for in vitro studies however two typical acute inflammation murine models (xylene-induced ear edema and carrageenan-induced paw edema) were used for anti-inflammatory studies. The important molecular mechanisms related to inflammation were also analyzed by ELISA, western blotting and immunofluorescence. UHPLC-MS/MS was used to analyze the chemical composition of 100% EAE fraction. Results: Different EAE fractions (especially the Fr. 100% of MeOH:H2 O) significantly reduced the productions of NO, ROS, TNF- α, and IL-6 by LPS-induced RAW264.7 macrophages and increased the expression of IL-10. The expression levels of iNOS and COX-2 enzymes were significantly down-regulated by 100% EAE fraction. Furthermore, 100% EAE fraction inhibited the phosphorylation of the ERK1/2, JNK, and p38 MAPK, and reduced the nuclear translocation of NF-κB which prevents its activation by blocking the phosphorylation and degradation of inhibitor protein of IκBα. In addition two inflammatory animal models; xylene-induced ear edema and carrageenan-stimulated paw edema were also developed with significantly ameliorated inflammatory cytokines. The treatment of these inflammatory models with 100% EAE fraction (Fr. 100%) suppressed the expressions of elevated inflammatory cytokines. Besides the UHPLC-HRMS/MS analysis was also carried out in which the androstane analogues were found to be as a main chemical components. Conclusion: Different fractions (especially Fr. 100%) exert inhibitory effect on inflammation by regulating the release of inflammatory mediators through the NF-κB and MAPK signaling pathways. The androstane and its derivatives might be performing an important role in the observed anti-inflammatory activity. Therefore, Fr. 100% of EAE could be applied as a potential drug candidate for the prevention and treatment of inflammatory diseases. Graphical abstract: Image 1 Highlights: Different EAE fractions reduced the productions of anti-inflammatory cytokines. Fr. 100% exhibited the strongest anti-inflammatory activity in vivo and vitro. Fr. 100% exerts anti-inflammatory effects by inhibiting NF-κB and MAPK pathways. The anti-inflammatory activity of Fr. 100% may be related to steroid compounds.